Effect of nitrogen fertilizer to growth, biomass and grain yield of paddy - Bejo, Siti Khairunniza; Zulkifli, Z.; Muharam, Farrah Melissa (International Society for Horticultural Science, 2017)
Nitrogen (N) fertilizer is an important plant nutrient for plant growth and yield. This study was conducted with four levels of N i.e., 0, 85, 170 and 250 kg ha-1using two rice cultivars i.e., 'MR219' and 'MR220'. The experiment was carried out in a factorial design with four replications and grown under flooded condition. The study focused on analysing the effect of N fertilizer level and cultivar to growth, biomass and grain yield. Statistical results showed that N significantly affected the plant height, SPAD reading, biomass and yield but did not affect the varieties. The interaction effect between the N level and cultivars also does not show significant difference. With the increment in N application, all parameters were also increased significantly. Maximum plant height (70.46 cm), SPAD reading (39.13), biomass (927.29 g m-2) and yield (830.99 g m-2) were obtained from 250 kg ha-1 nitrogen application. Correlation and regression analysis between plant heights, SPAD reading, biomass and grain yield exhibited a strong and positive relationship. The result also indicate that plant height is a better indicator to estimate biomass (R=0.794, R2=0.630) and grain yield (R=0.634, R2=0.397) compared to SPAD reading.